American Messiahs: The Narrative Strategies of FDR and Reagan, 1933 and 1981 - Theo Zenou (European Journal of American Studies)
This article investigates the rhetoric of Presidents Franklin D. Roosevelt and Ronald Reagan when they took office, in 1933 and in 1981, at two moments of crisis. More specifically, it compares and contrasts the stories the two presidents told the American people through their speeches. It finds that the stories had strong parallels: Roosevelt and Reagan both depicted America as a land in decay, and portrayed themselves as messiahs who would redeem the nation. Ultimately, this article argues that the presidents both used story as strategy. That is to say their stories had a political endgame. Indeed, Roosevelt’s and Reagan’s messianic stories were tools to help transform American political ethos, and in so doing foster support for their reform agendas.